Recidivism among juvenile delinquents: Self-reported sociodemografic characteristics, behavioural features and perceptions of delinquency - Kiriakidis, Stavros P. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
THE ABSTRACT IS AVAILABLE IN THE PDF